HISTOPATHOLOGICAL SPECTRUM OF OVARIAN TUMORS: A DESCRIPTIVE STUDY - Arora , Ajay Kumar (Journal of Biomedical and Pharmaceutical Research, 2018)
BACKGROUND: Because they are intricate and distinct organs, ovaries can develop a wide range of tumors involving different histological patterns, from epithelial tissue to specialized germinal and embryonal cells that secrete hormones. The second most prevalent gynecologic cancer and the fifth most frequent cancer among women is ovarian cancer. It is the most frequent reason for mortality from female genital tract cancer. About 4% of all female cancers and 25% of malignant tumors of the female genital tract are ovarian cancers. The ovary is the organ in the female genital system that is most commonly affected by cancer in India, after the cervix. Ninety percent of ovarian malignancies are malignant types, while two thirds of ovarian tumors are surface epithelial tumors. They exist in different histological patterns and exhibit varying degrees of aggressiveness.AIM: Evaluating the prevalence and distribution of several histological subtypes of ovarian neoplastic and non-neoplastic lesions was the study's main objective. MATERIAL AND METHOD: The Department of Pathology carried out this descriptive investigation. The 100 ovarian tumor specimens that were forwarded to the hospital's Department of Pathology for histological analysis were included in this study. A study was carried out using specimens that were regularly brought into the pathology department. They often obtained consent. The patient paid no additional costs for the tissue part under study. At every stage of the study, the patient's confidentiality was upheld. Standard techniques were followed to prepare fresh slides from the paraffin-embedded blocks and stain them for H and E. Gross findings were looked for in preserved gross specimens from the pathology department. From the histopathological record portion of the test requisition forms, information such as age and laterality were obtained.RESULTS: Out of the 100 ovarian diseases cases that were examined, 60 of them were non-neoplastic, while the other 40 were cancerous. Eighty out of the hundred tumors, or 90.6%, were found to be present between the third and sixth decade. Merely 10% of tumors were observed in those under 20 years old and those beyond 60 years old. Of the malignant lesions, 50.94% of the cases occurred in the age range of 20 to 39 years. Every age group experienced non-neoplastic lesions, although the 40–59 age group accounted for 56.66% of all occurrences, or the majority of instances. The tumors were primarily unilateral. Of the 100 tumors, 30 (or 28%) presented bilaterally.CONCLUSION: Benign tumors were more common than malignant ones in our study, and non-neoplastic ovarian lesions were more frequently observed than neoplastic lesions. Across all age categories, surface epithelial tumors were the most prevalent histologic type. As for ovarian cancer, serous adenocarcinoma was the most frequently observed type. When ovarian cancers reach an advanced stage, they behave like "Silent Killers." Ovarian lesions, whether malignant or non-neoplastic, frequently exhibit comparable clinical and radiological characteristics.KEYWORDS: Histopathology, Neoplastic, Non-Neoplastic Lesions, Ovarian Lesion, Sex Cord-Stromal Tumors, Germ Cell Tumors, and Surface Epithelial Tumors